IJCM_208A: Challenges in the uptake of testing for Tuberculosis Infection among household contacts of Index Tuberculosis patients: An operational analysis - Samudyatha UC; Kamath Prasanna BT (Wolters Kluwer Medknow Publications, 2024)
Background: Gaps in Tuberculosis Preventive Treatment (TPT) cascade among household contacts (HHCs) of Tuberculosis patients are often attributed to the knowledge gaps among the HHCs. Objectives: To examine the factors affecting the uptake of IGRA testing among HHCs of drug-susceptible, pulmonary TB patients registered between January and May 2023 in Kolar district, Karnataka using Health Belief model and qualitative interviews. Methodology: Between April and June 2023, 196 HHCs of 70 registered TB patients were included in the mixed methods study. Using a four-point Likert scale questionnaire, adult HHCs were interviewed regarding their knowledge of TB disease, perceived susceptibility and severity of TB Infection, benefits, and barriers in testing for TB Infection (IGRA) and cues for action. Mann Whitney U test was used to compare the scores of those who were tested and those who were not. Further, reasons for not undergoing IGRA testing were also assessed qualitatively. Results: Among 196 HHC, 45 were children under 5 years. IGRA testing had been done in 47% (71/151) of eligible HHCs. Among adult HHC, self- perceived and Index case-attributed susceptibility score was significantly associated with testing; while perceived severity scores, knowledge and perceived benefit scores were not. Major themes in barriers to testing were misinterpretation of 'TB Infection', selective testing of HHCs, delayed contact tracing, lack of logistics and lack of planning and coordination. TPT was given to 84% (38/45) under five HHCs. Major cue for TPT provision was availability of TPT, followed by caregiver's perceived susceptibility. Conclusion: Perceived susceptibility of HHC to TB infection is often misinformed. Group counselling of HHCs, provision of IGRA at doorstep and a well-established referral system will improve the uptake of IGRA.